Lab-scale production of postbiotic proteins from Bifidobacterium adolescentis with antiviral and epithelial-protective properties - Hernández, María; Quevedo, Balkys; Cabrera, María; Ulloa, Juan (Frontiers in Microbiology, 2025)
Postbiotics produced by probiotic bacteria are gaining attention as multifunctional, food-derived agents with potential applications in human and animal health. This study investigates the production and biological activity of protein-rich postbiotics from Bifidobacterium adolescentis, cultivated under controlled conditions in a 3-liter bioreactor as a laboratory-scale model for functional ingredient development. Culture parameters were improved, and one representative batch was selected for biological evaluation. The postbiotic preparation was tested for cytotoxicity using MA104 (renal) and C2BBe1 (intestinal) epithelial cell lines through viability and cell death assays, confirming its safety across a range of concentrations. To assess its functional activity, we evaluated its ability to reduce rotavirus infection and preserve epithelial integrity. The postbiotic significantly reduced viral infectivity and maintained cytoskeletal architecture in infected intestinal cells, supporting its potential protective role. These findings suggest that B. adolescentis-derived postbiotics may serve as safe and biologically active compounds with potential applications in intestinal health and viral infection management.